Director perspectives to equity, access, and inclusion in the school jazz ensemble - de Bruin, Leon R. (Frontiers in Education, 2022)
Arts and culture are increasingly acknowledged as pillars of society in which all of humanity including LGBTQIA+ can contribute in 21st century society. Within a globally competitive economy the notion of inclusive, egalitarian values promotes equal access and opportunity to chosen careers and passions. Jazz as an artform evolved as cultural expression, an entertainment both group-oriented and soloistically driven, carving both a canon and popularised history. Jazz education has moved from largely informal to almost wholly formal and institutionally designed methods of learning and teaching. The jazz ensemble or stage band remains an enduring secondary education experience for most students learning jazz today. This qualitative study of music directors investigates their approaches, perspectives and concerns regarding attitudes and practices in the profession, the promoting of inclusive practices, access and equity, amidst a pervasive masculinised performance and social structure. The study provides implications for how jazz education may continue to evolve in both attitude and access in the education of jazz learners.